DIGITAL SPIRITUAL WELL-BEING FOR ISLAMIC ELEMENTARY SCHOOL STUDENTS IN THE AGE OF ARTIFICIAL INTELLIGENCE - Muhammad Alfi Syahrin; Rifqi Khoiril Anam; Dody Tisna Amijaya; Rani Asmara (LPPM STAI Muhammadiyah Probolinggo, 2024)
The rapid advancement of Artificial Intelligence (AI) has fundamentally transformed educational practices and introduced new challenges to students’ well-being, particularly in the spiritual domain. Although studies on digital well-being and spiritual well-being have grown substantially in recent years, the integration of these concepts within Islamic education remains limited. This study aims to identify, analyze, and develop a conceptual framework of Digital Spiritual Well-Being for Islamic elementary school students in the age of AI. A Systematic Literature Review (SLR) approach was employed following the PRISMA 2020 guidelines. Data were collected from the Scopus database using the keywords “spiritual well-being” and “education.” The initial search yielded 1,357 articles, which were subsequently screened through predefined inclusion and exclusion criteria, resulting in 19 eligible studies for analysis. Data were examined using thematic content analysis. The findings revealed four major themes: (1) spiritual well-being as a foundation for mental health, meaning in life, and self-regulation; (2) family, Islamic schools, and religious environments as ecological foundations of spiritual well-being; (3) spiritual practices as strategies for strengthening emotional regulation, resilience, and digital awareness; and (4) the need for a Digital Spiritual Well-Being framework in the era of AI. Based on the literature synthesis, this study proposes five key dimensions of Digital Spiritual Well-Being: spiritual awareness, digital self-regulation, moral discernment, relational well-being, and meaningful digital engagement. The findings suggest that Islamic elementary education in the AI era should integrate spirituality, ethics, and digital competencies in a balanced manner to support students’ holistic developmentKeywords: digital distraction; learning concentration; Islamic elementary school; digital literacy; systematic literature review.